Regulatory Disharmony of Corporate Social Responsibility (CSR) between State-Owned and Private Enterprises and Its Implications for Sustainable Development Indicators in Indonesia: Disharmoni Pengaturan Corporate Social Responsibility (CSR) antara Badan Usaha Milik Negara dan Perusahaan Swasta serta Implikasinya terhadap Tolok Ukur Pembangunan Berkelanjutan di Indonesia - Andriani, Kasmita; Lie, Gunardi (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Corporate Social Responsibility (CSR) in Indonesia has transitioned toward the Triple Bottom Line, positioning CSR as a key driver of sustainable development. Specific Background: However, its implementation exhibits regulatory differences between State-Owned Enterprises (SOEs) and private companies, creating inconsistencies in legal obligations and funding mechanisms. Knowledge Gap: Existing CSR regulations emphasize formal compliance rather than measurable, sustainable impact, and little research examines how regulatory disharmony affects effectiveness. Aims: This study analyzes the juridical implications of regulatory disparities and evaluates CSR success benchmarks in relation to sustainable development principles. Results: Findings reveal two major implications: (1) discriminatory treatment, as CSR is mandatory for non–natural resource SOEs but voluntary for similar private firms, contradicting equality before the law; and (2) legal uncertainty due to conflicting norms on CSR funding sources. Additionally, a substantive gap appears between legal requirements and sustainability-oriented effectiveness indicators. Novelty: The study integrates legal analysis with sustainable development metrics, highlighting the need to shift CSR evaluation from compliance-based to impact-based frameworks. Implications: Harmonizing CSR regulation and adopting outcome-oriented benchmarks are essential to strengthen CSR’s contribution to Indonesia’s sustainable development agendas. Highlights: Regulatory inconsistencies create unequal CSR obligations between SOEs and private firms. Conflicting norms on funding sources generate legal uncertainty in CSR implementation. Effective CSR requires shifting from compliance-based evaluation to impact-based benchmarks. Keywords: CSR, Regulatory Disharmony, State-Owned Enterprises, Sustainable Development, Legal Uncertainty